Molecular origin and biological effects of exercise mimetics - Yuping Zhu; Gang Song (Elsevier, 2024)
With the rapid development of sports science and molecular biology technology, academia refers to molecules or microorganisms that mimic or enhance the beneficial effects of exercise on the body, called "exercise mimetics." This review aims to clarify the concept and development history of exercise mimetics, and to define the concept of exercise mimetics by summarizing its characteristics and functions. Candidate molecules and drug targets for exercise mimetics are summarized, and the relationship between exercise mimetics and exercise is explained, as well as the targeting system and function of exercise mimetics. The main targeting systems for exercise mimetics are the exercise system, circulatory system, endocrine system, endocrine system, and nervous system, while the immune system is potential targeting systems. Finally, future research directions for exercise mimetics are discussed.